1994
DOI: 10.1159/000117070
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems in Multiple Sclerosis

Abstract: Twenty-eight consecutive patients with multiple sclerosis (MS) were clinically evaluated to determine the presence of sleep-related disorders. There were 12 males and 16 females aged between 22 and 67 with disability ranging between 1.5 and 8.5 on Kurtzke extended disability status score (EDSS). Fifteen patients (54%) reported sleep-related problems. These included difficulties initiating sleep and/or frequent awakenings due to spasms or discomfort in the legs (8 patients), difficulty in initiating or maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 14 publications
8
110
1
4
Order By: Relevance
“…It has been reported that at least 50 % of patients with MS complain about sleep disturbances or poor sleep [5,84] The largest study included in our review comprised 2,375 MS patients and focused on the frequency of sleep disorders and their association with fatigue and sleepiness [31]. As assessed by the ESS, the prevalence of daytime sleepiness was reported to be 30%, while that for abnormal fatigue measures was 60%.…”
Section: The Impact Of Sleep Disordersmentioning
confidence: 99%
“…It has been reported that at least 50 % of patients with MS complain about sleep disturbances or poor sleep [5,84] The largest study included in our review comprised 2,375 MS patients and focused on the frequency of sleep disorders and their association with fatigue and sleepiness [31]. As assessed by the ESS, the prevalence of daytime sleepiness was reported to be 30%, while that for abnormal fatigue measures was 60%.…”
Section: The Impact Of Sleep Disordersmentioning
confidence: 99%
“…In a large study of more than thousand individuals with MS, prevalence of moderate or severe sleep problems was more than 50% [62]. The most common symptoms are difficulty initiating and maintaining sleep, frequent awakenings because of leg cramps and discomfort, snoring and nocturia [63]. Lack of sleep leads to increased fatigue, daytime somnolence and respiratory dysfunction episodes [64].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Stability of the MMMS scale over a period of 2 weeks to 3 months was measured by the intraclass cor- of difficulty falling asleep, frequent awakenings, snoring, and nocturia. 39 The factored subscale Cognitive/Mental explained 8.3% of the variance in the MMMS. Cognitive dysfunction has a prevalence of up to 65% of individuals with MS. 40 Cognitive areas most often affected are memory, attention, information processing, abstract/conceptual reasoning, and visuospatial skills.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions associated with fatigue among those with MS include mood and sleep disorders. Sleep disturbance, with a prevalence of 51.5%, 38 may be due to leg spasms, pain, immobility, nocturia, or medication 39 and can consist definitions of RRMS and SPMS, RRMS generally indicates disease relapses with full recovery or with sequelae and residual deficit upon recovery, while SPMS indicates progression with or without occasional relapses, minor remissions, and plateaus. 2 Some of the study participants may have been undergoing a transition in disease classification from RRMS to SPMS.…”
Section: Discussionmentioning
confidence: 99%